The Effect of Using the WhatsApp Digital Application on the Work Effectiveness of Polewali Mandar District Tourism Office Employees - Ihsan, Ahmad ihsan; Anwar; Haeruddin, M. Ikhwan Maulana (Kirana Publisher (KNPub), 2023)
Ahmad Ihsan (2022)